2013
DOI: 10.1016/j.pmatsci.2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Rare-earth mononitrides

Abstract: When the rare earth mononitrides (RENs) first burst onto the scientific scene in the middle of last century, there were feverish dreams that their strong magnetic moment would afford a wide range of applications. For decades research was frustrated by poor stoichiometry and the ready reaction of the materials in ambient conditions, and only recently have these impediments finally been overcome by advances in thin film fabrication with ultra-high vacuum based growth technology. Currently, the field of research … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
240
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(261 citation statements)
references
References 193 publications
(399 reference statements)
20
240
0
Order By: Relevance
“…The structural, magnetic and electronic properties of rare-earth monopnictides were reviewed recently [1,2]. In these reviews it was emphasized that the experimental data on the rare-earth monopnictides are rather scattered, and often lead to contradicting results, due to difficulties in obtaining samples of good quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural, magnetic and electronic properties of rare-earth monopnictides were reviewed recently [1,2]. In these reviews it was emphasized that the experimental data on the rare-earth monopnictides are rather scattered, and often lead to contradicting results, due to difficulties in obtaining samples of good quality.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, controversies concerning their electronic structure, transport and magnetic properties exist in literature. In the same reviews [1,2] the results of different electronic structure calculations of RN compounds were also compared. The description of the strongly correlated 4f states within the band theory is shown to require methods which go beyond density functional theory (DFT) in the standard local spin density approximation (LSDA).…”
Section: Introductionmentioning
confidence: 99%
“…One was reactive ball milling (Fritsch Ltd.: P-6) under an ammonia atmosphere and the other was high-pressure reactions (12)(13)(14) in an autoclave at 473-573 K for 48 h. In a typical preparation of cerium amide by ball milling [19], cerium dihydride (0.25 g) was placed in a grinding bowl (made of zirconia; volume of 45 cm 3 ), followed by introduction of 0.3 MPa ammonia. The mixtures were subjected to ball milling with zirconia balls (diameter: 3 mm, 55 g) for 0.25-20 h, operated at 650 rpm.…”
Section: Procedures Of Sample Preparationmentioning
confidence: 99%
“…There have been studies reported on many processes for the preparation of nitrides [14,15], but none is fully satisfactory for catalysts. The direct reaction of RE metals with ammonia or nitrogen at elevated temperatures is undesirable for the preparation of stoichiometric nitrides [16].…”
Section: Introductionmentioning
confidence: 99%
“…2 For a recent discussion and extensive overview of the literature, see Ref. 1. On the experimental side, this uncertainty is related to the difficulty in achieving purely stoichiometric 1:1 RE:N ratio.…”
Section: Introductionmentioning
confidence: 99%